Effects of synchronous versus asynchronous push modes on performance and biomechanical parameters in elite wheelchair basketball - Astier, M.; Weissland, T.; Vallier, J. M.; Pradon, D.; Watelain, E.; Faupin, A. (Sports Engineering, 2018)
This study aimed to compare the effects of synchronous (SYN) vs asynchronous (ASY) modes of wheelchair propulsion in field sprint tests on performance and biomechanical parameters. Seven elite wheelchair basketball players performed two separate (SYN and ASY) straight-line 20-m sprints. ASY increased sprint time and decreased push frequency compared to SYN (p < 0.05). Peak velocity and total force for the mean of the last three pushes were higher in SYN. Rate of rise was higher in SYN for the first, second and third pushes (p < 0.05). No significant difference was found for peak power and mean work. SYN mode induces better performance (13% difference in speed). However, the increase in rate of rise, thus the expansion of the total force when gripping the hand rim, push frequency and total force in SYN modes seems to expand the risk of developing musculoskeletal disorders during manual wheelchair propulsion for upper limb joints than ASY.